Pengaruh Pengetahuan Perbankan Syariah dan Religiusitas Terhadap Minat Berkarir di Perbankan Syariah dengan Sikap sebagai Variabel Moderasi - Sulistiyowati, Tri Indah; Hakim, Luqman (Universitas Pendidikan Ganesha, 2021)
Careers for graduates of accounting education study programs are not only limited to accounting teacher but also careers in islamic banking. The aims of this study is to analyze the influence of the variables of islamic banking knowledge and religiosity on career Interest in islamic banking, reinforced by the moderating variable of the attitude. The subject or population of this study is students of State University of Surabaya, accounting education study program. The sample was determined using a purposive sampling method with a total sample of 158 respondents. The questionnaire is a data collection method used. The results of data analysis through WarpPLS show that knowledge of islamic banking directly, positifly, and significantly influences career interest in islamic banking. Religiosity does not directly affect career interest in islamic banking. Attitude can strengthens the influence of islamic banking knowledge on career interest in islamic banking but cannot moderate the influence of religiosity on career interest in islamic banking.Â